THE INVESTIGATION OF INDONESIAN EFL LEARNERS’ ERRORS ACROSS THREE PROFICIENCY LEVELS - Saudin Saudin (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2017)
The study analyzed the errors made by students across three different levels of proficiency (Advanced, Intermediate and Elementary) in their writing pieces. Three students were selected purposively to represent their respective level. So, nine pieces of writing altogether were to be investigated in this study. The errors committed by the purposive samples were first grouped into fifteen linguistic classifications such as verb form, preposition, mechanics and so forth, then subsumed under two broader categories: negative interlingual and intralingual transfer. The investigation revealed that the learners made more errors of intralingual transfer than those of negative interlingual one. However, in terms of errors based on the linguistic classifications, this study showed surprising findings. Advanced learners, though committing the least errors, performed worst by making errors in the most linguistic classifications (seven altogether): plural-singular form, omission of constituent, verb form, article, vocabulary, pronoun and comparative. Intermediate learners came next by committing errors in less number of linguistic areas (five), namely mechanics, preposition, derivative, auxiliary verb and clause formation. Elementary learners came last by giving poor performances on the least number of just three linguistic areas: tense, word order and genetives. Across levels, however, three areas (consecutively mechanics, plural/singular form and omission of constituent) appeared to be where errors were most commonly committed. With findings as such, the study is expected to impart theoretical contributions to SLA, especially to studies on error analysis. The findings hopefully can also inspire teachers to teach students of these three proficiency levels in ways that meet their needs more. Keywords: purposive samples, linguistic classifications, negative interlingual tranfer, intralingual transfer, SLA.